2015
DOI: 10.1891/1058-1243.24.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Length of Labor and Cesarean Surgery Rate Using a Peanut Ball for Women Laboring With an Epidural

Abstract: One strategy for reducing the primary cesarean surgery rate and length of labor is using a peanut-shaped exercise ball for women laboring under epidural analgesia. A randomized, controlled study was conducted to determine whether use of a "peanut ball" decreased length of labor and increased the rate of vaginal birth. Women who used the peanut ball (n = 107) versus those who did not (n = 91) demonstrated shorter first stage labor by 29 min (p = .053) and second stage labor by 11 min (p < .001). The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 36 publications
0
36
0
8
Order By: Relevance
“…Labor is influenced by several factors, namely age, parity, the distance of pregnancy, education, and mother's knowledge [8]. [9] in their results showed a significant relationship between age and parity with the length of labor as indicated by the p-value of 0.001. Based on the table above, it can be seen the difference in the 1st stage in the treatment group compared to the control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Labor is influenced by several factors, namely age, parity, the distance of pregnancy, education, and mother's knowledge [8]. [9] in their results showed a significant relationship between age and parity with the length of labor as indicated by the p-value of 0.001. Based on the table above, it can be seen the difference in the 1st stage in the treatment group compared to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Surtiningsih, et al (2016) [6] research shows that Pelvic Rocking Exercises are very effective in shortening the length of time in the first phase of active phase with a value of ρ-value of 0,0001. Hassan Zaky, Nevertity (2016) [12] in his research mentioned that there were significant differences in the duration of the first stage of labor in the control group and the treatment group Birth ball training was given with a pvalue of 0,000 Tussey CM, et al (2015) [9] in the results of their study showed a significant difference between the duration of the first stage of labor in the control group and the treatment group was given birth balls. This exercise significantly increased the acceleration rate of stage 1 by 29 minutes compared to the control group.…”
Section: The Length Of the 1st Stagementioning
confidence: 99%
See 1 more Smart Citation
“…2 Comment by Robert Gaiser, MD, MSEd Disclosure: The author declares no conflict of interest. Cesarean delivery represents the most common surgical procedure performed in the United States.…”
Section: Commentmentioning
confidence: 99%
“…One randomized controlled trial (RCT) found use of the peanut ball in active labor reduced length of both the first stage and second stage of labor in a combined group of multiparous and nulliparous patients with epidurals; this study also reported a reduction in the incidence of cesarean delivery. 15 A second RCT showed a reduction in the first stage of labor for patients undergoing induction of labor only for nulliparous patients, with no difference in labor course for multiparous patients, and no difference in rates of cesarean. 16 We performed a randomized trial to investigate the impact of peanut ball use on the duration of active phase labor, incidence of cesarean delivery, and incidence of fetal occiput posterior position at time of delivery in a cohort of nulliparous women with epidurals.…”
Section: Introductionmentioning
confidence: 99%